Sustainable consumption futures: according to whom? - Åsa Svenfelt; Noha Baraka Wadha; Vishal Parekh (Sustainability: Science, Practice, & Policy)
This article aims to uncover diverse perspectives regarding what sustainable consumption is and should be in the future. We draw upon and combine critical futures studies with recognitional justice. Futures studies enables inclusive approaches and divergence from current narratives of the future that are perceived as dominant. Recognitional justice allows for reflection upon who is usually not in the room when consumption futures are discussed. The article analyzes sustainable consumption-futures workshops held with four groups in Sweden. The first was with partners in a research program focusing on sustainable consumption. The second workshop enlisted elderly rural retirees, the third newly-arrived women from Syria and Eritrea, and the fourth high-income earners. A variety of traits in the discussions were noticeably influenced by the local context and backgrounds of the participants. Several issues brought up in the discussions dealt with issues that are on the political agenda in Sweden, such as circulating materials and more information and knowledge. There were also matters not on the political agenda such as eating a vegetarian diet, reducing consumption, and spending less time working. In addition, the newly-arrived women and, to some extent, the retirees, framed peace and ending the use of weapons as a vital element in sustainable consumption. This diversity and divergence highlights that, if it is to become relevant and inclusive, both research and policy need to recognize a multitude of perspectives and incorporate the distribution of power and critical futures perspectives to navigate a pathway toward consumption that is just and sustainable.